(untitled) (The Pakistan Development Review, 2007)
The book is about business interests of the military in Pakistan. It looks at the political economy of military’s business activities and the personal economic stakes of military personnel as the driver of political ambitions of the armed forces. The author has coined the term ‘Milbus’ for military’s business activities. She defines ‘Milbus’ as ‘military capital used for the personal benefit of military fraternity’. Apart from the Introduction, the book has ten chapters. Chapter 1, ‘Milbus: A Theoretical Concept’, argues that Milbus prevails in most militaries around the world. The extent to which Milbus prevails in a military depends upon the civil-military relations and the strength of political institutions in the country. The chapter outlines six distinct categories of civil-military relations along a continuum of the strength of civil institutions. Polity’s that boast of strong civil institutions, see political forces rule over the country with military playing a subservient role. As the strength of civil institutions declines, militaries penetrate, with the role military becoming complete when the state fails. This is the state where warlords rule. Chapter 2, ‘The Pakistan Military: The Development of Praetorianism’, argues that certain structural lacunae in Pakistan’s political system, dating back to 1947, brought the military to fore. Governments of the day, having failed to promote socioeconomic development, promoted the national security paradigm, to retain their political legitimacy. This brought the military to the forefront. The ascent of military is owed on the one hand to the weak political leadership, that gave the military an opportunity to assert itself, and on the other hand to the authoritarian inclination of civil governments, that compelled these governments to partner with the military. Thus the seed of praetorianism were sown from the very beginning.